European Pension Systems – the Real Challenge of the 21st Century - Maria Augusztinovics (Romanian Journal of European Affairs)
It will be argued that the present focus of the pension reform debate – public, pay-as-you-go versus private, funded – is misplaced and somewhat outdated. Pay-as-you-go versus funding or pre-funding is a more-or-less technical issue. The public versus private choice should be seen as a cost-benefit, efficiency problem. These two dichotomies represent important, but secondary problems. (They cannot even be expected to help solving the certainly serious – although not that catastrophic as often painted – problems caused by the foreseeable demographic changes, the so-called ageing of the population.) The major distinctive attribute of existing European pension schemes is not the mode of financing or management. It is the Bismarckian heritage, the close link to employment, based on the typically 20th century-type, continuous working career. A presently emerging trend, however, is the transformation of the labour market. The so-called „atypical” forms of employment (part-time work, outsourcing, work at home, fixed-length contracts, etc.) are spreading and the traditional employer-employee link is weakening, if not – at least partially – disappearing. Activity ratios (poorly represented by the unemployment rate) are declining. This trend will probably be accentuated by the deepening of globalization and European integration, the growing importance of migration, including temporary migration (i.e. working in one country for a few years, then in another one, then maybe returning home for retirement). The questions thus arise: how, when, where will people, who are economically „inactive” or wandering around during a large faction of their earning span, acquire pension eligibility, sufficient for income security in old age? Will the present forms of pension insurance (including social security as well as country-based private funds) be able to live up to this 21st century-type of challenge? If not, what are the adequate models for the future and what are the feasible ways of transition to them? How much and what type of European harmonization of pension systems is and will be required? (For example, how could a harmonized European system react to country-specific mortality rates and to the emerging problem of the „oldest old”?) The paper is intended to discuss these and several related issues.